Intrusive Beauty : Poems - Capista, Joseph J. (Book collections on Project MUSE., 2019)
"Joseph J. Capista's Intrusive Beauty reckons with reluctant ecstasy and the improbable forms that beauty assumes. In this powerful debut, Capista traverses earth and ether to yield poems that elucidate the space between one's life and one's livelihood. While its landscapes range from back-alley Baltimore to the Bitterroot Valley, this book remains close to unbidden beauty and its capacity to sway one's vision of the world. Whether a young father who won't lower the volume on the radio or a Victorian farm boy tasked with scaring birds from seed-sown furrows, the inhabitants of Intrusive Beauty are witness to the startling ease with which one's assorted lives come in time to comprise a singular life. Mortality, love, duty, desire, an acute longing for transcendence: here, old themes resound anew as they're uttered in a multiplicity of forms and means, holding fast always to the heart"--